DISMISSAL OF NEW YORK UNION CASES - COGGINS,C; REILLY,J (Tufts Archival Research Center, 2007)
Memo from Jack Reilly to Lorillard R&D on dismissal of New York union lawsuits filed to recover health care expenses. Summarizes decision by Justice Edward Ramos of New York State Supreme Court dismissing 14 union fund suits in response to Lorillard motion. Discusses issue of third-party cost recovery, and that indirect damage to union funds is insufficient grounds for suit. Also invokes statute of limitations.